A green and environmentally friendly waterproof coating and preparation method thereof

By adding chain network glass scales to water -based polyurethane coatings to form a multi -layered parallel arrangement and complex staggered structure, the problem of poor performance in waterproof and corrosion of water -based polyurethane coatings, realizing significant improvement of anti -permeability and waterproof effect. Effect.

CN118185446BActive Publication Date: 2025-01-28HEBEI LANDCEL CELLULOSE TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410390999.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-02
Publication Date
2025-01-28
Estimated Expiration
2044-04-02

AI Technical Summary

Technical Problem

Water-based polyurethane coatings have poor performance in waterproofing and corrosion protection. The prior art improves density by adding nanofillers but cannot form an effective waterproof barrier.

Method used

Add chain mesh glass scales to water -based polyurethane coatings. By forming a multi -layer parallel arrangement structure and complex cross -chain network structure in the coating, it forms two waterproof barriers and improves resistance.

Benefits of technology

The addition of the chain network glass scales significantly improves the resistance and waterproof effect of the coating, forming two waterproof barriers, and enhancing the strength and waterproof performance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118185446B_ABST
    Figure CN118185446B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of waterproof coatings, specifically to a green and environmentally friendly waterproof coating and a preparation method thereof, comprising: (1) injecting an aqueous polyurethane emulsion into a stirring kettle, and adding a film-forming aid, a leveling agent and a defoaming agent into the stirring kettle, and stirring evenly; (2) adding chain-net glass flakes into the stirring kettle in batches for stirring and dispersion, and then adding a thickener and continuing to stir to obtain a green and environmentally friendly waterproof coating. The chain-net glass flakes added in the present invention will form a multi-layer parallel arrangement structure in the matrix, and produce a sealing effect by overlapping and overlapping, and the tortuous permeation path has good permeability resistance, forming a first waterproof barrier; at the same time, through dopamine polymerization and bonding with a silane coupling agent, modified carbon fibers can be grafted onto the surface of the glass flakes to form a complex and staggered chain-net structure, producing a maze-like effect, and the second waterproof barrier formed further improves the permeability resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of waterproof coatings, and in particular to a green and environment-friendly waterproof coating and a preparation method thereof. Background Art

[0002] Waterborne polyurethane coatings use water as a dispersion medium and are widely used for their flame retardancy, non-toxicity, environmental friendliness, and environmental friendliness. However, compared with solvent-based polyurethane coatings, the crosslinking density of waterborne polyurethane coatings is relatively low, resulting in poor performance of waterborne polyurethane coatings in terms of waterproofing and corrosion resistance. At present, in order to improve the permeability resistance of waterborne polyurethane coatings, nanofillers modified with coupling agents are added to the matrix. The uniform dispersion and filling of nanofillers in the matrix can improve the permeability resistance to a certain extent. Although the use of nanofillers can improve the density of the final coating, it is unable to form a waterproof barrier layer in the final coating, and the improvement of the permeability resistance of waterborne polyurethane coatings is limited. Summary of the invention

[0003] In order to address the deficiencies in the prior art, the present invention provides a green and environmentally friendly waterproof coating and a preparation method thereof. The added chain-mesh glass flakes will form two waterproof barriers in the molded coating, thereby improving the coating's anti-penetration property and achieving a good waterproof effect.

[0004] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a green and environmentally friendly waterproof coating, comprising the following raw materials in parts by weight: 60-80 parts of water-based polyurethane emulsion, 20-30 parts of chain-mesh glass flakes, 2-5 parts of film-forming aid, 1-3 parts of leveling agent, 1-2 parts of defoaming agent, and 0.5-1 part of thickener.

[0005] Preferably, the film-forming aid includes but is not limited to propylene glycol butyl ether and benzyl alcohol; the leveling agent includes but is not limited to cellulose acetate-butyrate and polydimethylsiloxane; the thickener includes but is not limited to hydroxypropyl methylcellulose and hydroxyethyl cellulose; and the defoamer is a silicone defoamer.

[0006] Preferably, the preparation method of chain-mesh glass flakes is as follows: S1. Coating a nano-silica layer on the surface of carbon fiber, and treating it with a silane coupling agent, and obtaining modified carbon fiber after drying; S2. Pour dopamine alkaline solution and glass flakes into a reaction chamber, and air continuously forms bubbles through a bubbling disk and is introduced into the reaction chamber for stirring, maintaining an aerobic alkaline environment, and reacting at room temperature for 2-3 hours; S3. Pour the modified carbon fiber into the reaction chamber and add an appropriate amount of silane coupling agent, continue the bubbling reaction for 3-5 hours, and obtain a mixed liquid containing chain-mesh glass flakes; S4. Filter, wash, and dry the mixed liquid containing chain-mesh glass flakes to obtain chain-mesh glass flakes.

[0007] Preferably, in step S1, the method for coating the surface of the carbon fiber with a nano-silicon dioxide layer is as follows: disperse the carbon fiber in a silicate solution, spray an 8wt% sulfuric acid solution on its surface after filtering, and react at 40-50°C for 30-40 minutes; repeat the above operation 2-4 times, and then dry to obtain.

[0008] Preferably, the silicate solution is prepared by mixing 5 wt % sodium silicate solution and 15 wt % sodium chloride solution in a volume ratio of 3:2.

[0009] Preferably, in steps S1-S2, the thickness of the glass flakes is 5-8 μm, and the diameter of the flakes is 200-250 μm; the length of the carbon fiber is 20-50 μm.

[0010] Preferably, in step S2, the dopamine base solution is prepared as follows: Tris hydrochloride (tris(hydroxymethyl)aminomethane hydrochloride) is dissolved in deionized water, the pH is adjusted to 8.5, and then dopamine is added and ultrasonically dispersed to obtain the solution.

[0011] Preferably, the material-liquid ratio of Tris hydrochloride to deionized water is 1:1000 g / ml, and the mass ratio of Tris hydrochloride to dopamine is 1:1.

[0012] Preferably, in steps S2-S3, the mass ratio of the modified carbon fiber to the glass flakes is 1:(2-4); and the volume ratio of the silane coupling agent to the dopamine alkaline solution is 1:15.

[0013] The present invention also provides a method for preparing a green and environmentally friendly waterproof coating, comprising the following steps:

[0014] (1) injecting the waterborne polyurethane emulsion into a stirring tank, and adding a film-forming aid, a leveling agent and a defoaming agent into the stirring tank, and stirring evenly;

[0015] (2) The chain mesh glass flakes are added to a stirring kettle in batches for stirring and dispersion, and then a thickener is added and continued to be stirred to obtain a green and environmentally friendly waterproof coating.

[0016] The present invention provides a green and environmentally friendly waterproof coating and a preparation method thereof, which has the following beneficial effects compared with the prior art:

[0017] The chain-mesh glass flakes added in the present invention will form a multi-layer parallel arrangement structure in the matrix, which produces a sealing effect through overlapping and overlapping, and the tortuous permeation path also has good permeability resistance, forming a first waterproof barrier; at the same time, through dopamine polymerization and bonding with silane coupling agent, the modified carbon fiber can be grafted on the surface of the glass flakes to form a complex and interlaced chain-mesh structure on its surface, producing a maze-like effect, extending the permeation path of the medium, and forming a second waterproof barrier that further improves the permeability resistance.

[0018] The present invention repeatedly coats the surface of the carbon fiber with nano-silicon dioxide to form a dense nano-silicon dioxide layer on the surface, which has good hydrophobicity and solves the problem of the carbon fiber's own brittleness, thereby improving the strength and waterproofness of the coating.

[0019] The present invention first preliminarily polymerizes dopamine on the surface of glass flakes, then adds modified carbon fibers, continues the polymerization reaction through dopamine, and the silane coupling agent on the surface of the carbon fibers bonds with dopamine, so that the modified carbon fibers are tightly linked to the glass flakes, thereby forming a complex and staggered chain-net structure.

[0020] The present invention also uses a chain mesh glass flake manufacturing machine, which provides a good aerobic alkaline environment and is helpful for linking the modified carbon fiber and the glass flake. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0022] Figure 1 It is a schematic structural diagram of the chain-net type glass flake manufacturing machine of the present invention. DETAILED DESCRIPTION

[0023] The following examples are used to explain the implementation methods of the present application in detail, so that the implementation process of how the present application uses technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly.

[0024] Example 1

[0025] like Figure 1 As shown, a chain-net glass flake manufacturing machine is mainly composed of a reaction chamber and multiple groups of bubbling disks, which are installed at the bottom of the reaction chamber. A shunt pipe and an air inlet pipe are buried in the manufacturing machine, and multiple groups of bubbling disks are connected and installed with the shunt pipe, and a blower is installed on the air inlet pipe. After pouring the dopamine alkaline solution and glass flakes into the reaction chamber, the blower is started to control the flow through the air inlet pipe and the shunt pipe and finally spray out from the bubbling disk. The bubbles formed can well disturb the fluid, allowing dopamine to start polymerizing on the surface of the glass flakes, and directly supply oxygen into the fluid, providing a good environment for dopamine polymerization. Then, modified carbon fiber and silane coupling agent are added. Under the stirring of bubbles, the modified carbon fiber gradually adheres to the surface of the glass flakes, forming a chain net on the surface of the glass flakes. The mixed liquid is filtered, washed, and dried to obtain chain-net glass flakes.

[0026] Example 2

[0027] A green and environment-friendly waterproof coating comprises the following raw materials in parts by weight: 80 parts of waterborne polyurethane emulsion, 20 parts of chain-net glass flakes, 5 parts of propylene glycol butyl ether, 1 part of cellulose acetate-butyrate, 2 parts of silicone defoamer, and 0.5 part of hydroxypropyl methylcellulose.

[0028] The preparation method of the green environmentally friendly waterproof coating comprises the following steps:

[0029] (1) injecting the aqueous polyurethane emulsion into a stirring tank, and adding propylene glycol butyl ether, cellulose acetate-butyrate and silicone defoamer into the stirring tank, and stirring evenly;

[0030] (2) The chain mesh glass flakes are added to a stirring kettle in batches for stirring and dispersion, and then hydroxypropyl methylcellulose is added and continued to be stirred to obtain a green and environmentally friendly waterproof coating.

[0031] Among them, the preparation method of chain mesh glass flakes is as follows:

[0032] S1, coating the surface of carbon fiber with a nano-silicon dioxide layer, treating it with a silane coupling agent KH-560, and obtaining a modified carbon fiber after drying;

[0033] The method for coating the surface of carbon fiber with a nano-silica layer is as follows: disperse carbon fiber with a length of 20-50 μm in a silicate solution, which is prepared by 5% sodium silicate solution and 15wt% sodium chloride solution in a volume ratio of 3:2, and then spray 8wt% sulfuric acid solution on its surface after filtering, and react at 40°C for 40 minutes; repeat the above operation twice, and then dry to obtain.

[0034] S2, pouring dopamine alkaline solution and glass flakes into the reaction chamber, wherein the thickness of the glass flakes is 5-8 μm and the diameter of the flakes is 200-250 μm, and air is continuously bubbled through the bubbling disk and introduced into the reaction chamber for stirring, maintaining an aerobic alkaline environment, and reacting at room temperature for 2 hours;

[0035] The dopamine base solution is prepared as follows: Tris hydrochloride is dissolved in deionized water at a solid-liquid ratio of 1:1000 g / ml, the pH is adjusted to 8.5, and then dopamine in an amount equal to the mass of Tris hydrochloride is added and ultrasonically dispersed to obtain the solution.

[0036] S3, pour the modified carbon fiber into the reaction chamber and add an appropriate amount of silane coupling agent KH-560, continue bubbling reaction for 3 hours, and obtain a mixed solution containing chain-net glass flakes;

[0037] The mass ratio of modified carbon fiber to glass flake is 1:2; the volume ratio of silane coupling agent KH-560 to dopamine alkaline solution is 1:15.

[0038] S4. Filter, wash and dry the mixed liquid containing chain-net glass flakes to obtain chain-net glass flakes.

[0039] In this embodiment, the manufacturing machine in Embodiment 1 is used.

[0040] Example 3

[0041] A green and environment-friendly waterproof coating comprises the following raw materials in parts by weight: 80 parts of waterborne polyurethane emulsion, 20 parts of chain-net glass flakes, 2 parts of benzyl alcohol, 3 parts of polydimethylsiloxane, 1 part of organosilicon defoaming agent and 1 part of hydroxyethyl cellulose.

[0042] The preparation method of the green environmentally friendly waterproof coating comprises the following steps:

[0043] (1) injecting the aqueous polyurethane emulsion into a stirring tank, and adding benzyl alcohol, polydimethylsiloxane and an organosilicon defoamer into the stirring tank, and stirring evenly;

[0044] (2) The chain mesh glass flakes are added into a stirring kettle in batches for stirring and dispersion, and then hydroxyethyl cellulose is added and continued to be stirred to obtain a green and environmentally friendly waterproof coating.

[0045] Among them, the preparation method of chain mesh glass flakes is as follows:

[0046] S1, coating the surface of carbon fiber with a nano-silicon dioxide layer, treating it with a silane coupling agent KH-560, and obtaining a modified carbon fiber after drying;

[0047] The method for coating the surface of carbon fiber with a nano-silica layer is as follows: disperse carbon fiber with a length of 20-50 μm in a silicate solution, which is prepared by 5% sodium silicate solution and 15wt% sodium chloride solution in a volume ratio of 3:2, and then spray 8wt% sulfuric acid solution on its surface after filtering, and react at 50°C for 30 minutes; repeat the above operation 4 times, and then dry to obtain.

[0048] S2, pouring dopamine alkaline solution and glass flakes into the reaction chamber, wherein the thickness of the glass flakes is 5-8 μm and the diameter of the flakes is 200-250 μm, and air is continuously bubbled through the bubbling disk and introduced into the reaction chamber for stirring, maintaining an aerobic alkaline environment, and reacting at room temperature for 3 hours;

[0049] The dopamine base solution is prepared as follows: Tris hydrochloride is dissolved in deionized water at a solid-liquid ratio of 1:1000 g / ml, the pH is adjusted to 8.5, and then dopamine in an amount equal to the mass of Tris hydrochloride is added and ultrasonically dispersed to obtain the solution.

[0050] S3, pour the modified carbon fiber into the reaction chamber and add an appropriate amount of silane coupling agent KH-560, continue bubbling reaction for 5 hours, and obtain a mixed solution containing chain-net glass flakes;

[0051] The mass ratio of modified carbon fiber to glass flake is 1:4; the volume ratio of silane coupling agent KH-560 to dopamine alkaline solution is 1:15.

[0052] S4. Filter, wash and dry the mixed liquid containing chain-net glass flakes to obtain chain-net glass flakes.

[0053] In this embodiment, the manufacturing machine in Embodiment 1 is used.

[0054] Example 4

[0055] A green and environment-friendly waterproof coating comprises the following raw materials in parts by weight: 70 parts of waterborne polyurethane emulsion, 25 parts of chain-net glass flakes, 4 parts of propylene glycol butyl ether, 2 parts of cellulose acetate-butyrate, 1.5 parts of silicone defoamer, and 0.6 parts of hydroxyethyl cellulose.

[0056] The preparation method of the green environmentally friendly waterproof coating comprises the following steps:

[0057] (1) injecting the aqueous polyurethane emulsion into a stirring tank, and adding propylene glycol butyl ether, cellulose acetate-butyrate and silicone defoamer into the stirring tank, and stirring evenly;

[0058] (2) The chain mesh glass flakes are added into a stirring kettle in batches for stirring and dispersion, and then hydroxyethyl cellulose is added and continued to be stirred to obtain a green and environmentally friendly waterproof coating.

[0059] Among them, the preparation method of chain mesh glass flakes is as follows:

[0060] S1, coating the surface of carbon fiber with a nano-silicon dioxide layer, treating it with a silane coupling agent KH-560, and obtaining a modified carbon fiber after drying;

[0061] The method for coating the surface of carbon fiber with a nano-silica layer is as follows: disperse carbon fiber with a length of 20-50 μm in a silicate solution, which is prepared by 5% sodium silicate solution and 15wt% sodium chloride solution in a volume ratio of 3:2, and then spray 8wt% sulfuric acid solution on its surface after filtering, and react at 45°C for 35 minutes; repeat the above operation 3 times, and then dry to obtain.

[0062] S2, pouring dopamine alkaline solution and glass flakes into the reaction chamber, wherein the thickness of the glass flakes is 5-8 μm and the diameter of the flakes is 200-250 μm, and air is continuously bubbled through the bubbling disk and introduced into the reaction chamber for stirring, maintaining an aerobic alkaline environment, and reacting at room temperature for 2.5 hours;

[0063] The dopamine base solution is prepared as follows: Tris hydrochloride is dissolved in deionized water at a solid-liquid ratio of 1:1000 g / ml, the pH is adjusted to 8.5, and then dopamine in an amount equal to the mass of Tris hydrochloride is added and ultrasonically dispersed to obtain the solution.

[0064] S3, pour the modified carbon fiber into the reaction chamber and add an appropriate amount of silane coupling agent KH-560, continue bubbling reaction for 4 hours, and obtain a mixed solution containing chain-net glass flakes;

[0065] The mass ratio of modified carbon fiber to glass flake is 1:3; the volume ratio of silane coupling agent KH-560 to dopamine alkaline solution is 1:15.

[0066] S4. Filter, wash and dry the mixed liquid containing chain-net glass flakes to obtain chain-net glass flakes.

[0067] In this embodiment, the manufacturing machine in Embodiment 1 is used.

[0068] Comparative Example 1

[0069] It is basically the same as Example 4, except that: the preparation method of the chain mesh glass flakes is as follows:

[0070] S1. Treating the surface of carbon fiber with a length of 20-50 μm with silane coupling agent KH-560, and obtaining modified carbon fiber after drying;

[0071] S2, pouring dopamine alkaline solution and glass flakes into the reaction chamber, wherein the thickness of the glass flakes is 5-8 μm and the diameter of the flakes is 200-250 μm, and air is continuously bubbled through the bubbling disk and introduced into the reaction chamber for stirring, maintaining an aerobic alkaline environment, and reacting at room temperature for 2.5 hours;

[0072] The dopamine base solution is prepared as follows: Tris hydrochloride is dissolved in deionized water at a solid-liquid ratio of 1:1000 g / ml, the pH is adjusted to 8.5, and then dopamine in an amount equal to the mass of Tris hydrochloride is added and ultrasonically dispersed to obtain the solution.

[0073] S3, pour the modified carbon fiber into the reaction chamber and add an appropriate amount of silane coupling agent KH-560, continue bubbling reaction for 4 hours, and obtain a mixed solution containing chain-net glass flakes;

[0074] The mass ratio of modified carbon fiber to glass flake is 1:3; the volume ratio of silane coupling agent KH-560 to dopamine alkaline solution is 1:15.

[0075] S4. Filter, wash and dry the mixed liquid containing chain-net glass flakes to obtain chain-net glass flakes.

[0076] Comparative Example 2

[0077] The same as Example 4, except that: the preparation method of the modified glass flakes is as follows:

[0078] S1, treating nano-silicon dioxide with a silane coupling agent KH-560, and obtaining modified nano-silicon dioxide after drying;

[0079] S2, pouring dopamine alkaline solution and glass flakes into the reaction chamber, wherein the thickness of the glass flakes is 5-8 μm and the diameter of the flakes is 200-250 μm, and air is continuously bubbled through the bubbling disk and introduced into the reaction chamber for stirring, maintaining an aerobic alkaline environment, and reacting at room temperature for 2.5 hours;

[0080] The dopamine base solution is prepared as follows: Tris hydrochloride is dissolved in deionized water at a solid-liquid ratio of 1:1000 g / ml, the pH is adjusted to 8.5, and then dopamine in an amount equal to the mass of Tris hydrochloride is added and ultrasonically dispersed to obtain the solution.

[0081] S3, pour the modified nano-silica into the reaction chamber and add an appropriate amount of silane coupling agent KH-560, continue bubbling reaction for 4 hours, and obtain a mixed solution containing modified glass flakes;

[0082] The mass ratio of modified nano-silica to glass flakes is 1:3; the volume ratio of silane coupling agent KH-560 to dopamine alkaline solution is 1:15.

[0083] S4. Filter, wash and dry the mixed liquid containing modified glass flakes to obtain modified glass flakes.

[0084] Comparative Example 3

[0085] A green and environment-friendly waterproof coating comprises the following raw materials in parts by weight: 70 parts of waterborne polyurethane emulsion, 25 parts of silane coupling agent KH-560 modified glass flakes, 4 parts of propylene glycol butyl ether, 2 parts of cellulose acetate-butyrate, 1.5 parts of organosilicon defoaming agent and 0.6 parts of hydroxyethyl cellulose.

[0086] The preparation method of the green environmentally friendly waterproof coating comprises the following steps:

[0087] (1) injecting the aqueous polyurethane emulsion into a stirring tank, and adding propylene glycol butyl ether, cellulose acetate-butyrate and silicone defoamer into the stirring tank, and stirring evenly;

[0088] (2) Adding glass flakes modified with silane coupling agent KH-560 and carbon fibers modified with silane coupling agent KH-560 in batches into a stirring kettle for stirring and dispersion, and then adding hydroxyethyl cellulose and continuing to stir to obtain a green and environmentally friendly waterproof coating.

[0089] Comparative Example 4

[0090] A green and environment-friendly waterproof coating comprises the following raw materials in parts by weight: 70 parts of waterborne polyurethane emulsion, 13 parts of glass flakes modified by silane coupling agent KH-560, 12 parts of carbon fibers modified by silane coupling agent KH-560, 4 parts of propylene glycol butyl ether, 2 parts of cellulose acetate-butyrate, 1.5 parts of silicone defoaming agent and 0.6 parts of hydroxyethyl cellulose.

[0091] The preparation method of the green environmentally friendly waterproof coating comprises the following steps:

[0092] (1) injecting the aqueous polyurethane emulsion into a stirring tank, and adding propylene glycol butyl ether, cellulose acetate-butyrate and silicone defoamer into the stirring tank, and stirring evenly;

[0093] (2) Adding glass flakes modified with silane coupling agent KH-560 and carbon fibers modified with silane coupling agent KH-560 in batches into a stirring kettle for stirring and dispersion, and then adding hydroxyethyl cellulose and continuing to stir to obtain a green and environmentally friendly waterproof coating.

[0094] Comparative Example 5

[0095] The method is basically the same as Example 4, except that: the method for coating the surface of the carbon fiber with a nano-silica layer is as follows: carbon fibers with a length of 20-50 μm are dispersed in a silicate solution, the silicate solution is prepared by 5% sodium silicate solution and 15wt% sodium chloride solution in a volume ratio of 3:2, and after filtering, 8wt% sulfuric acid solution is sprayed on the surface, and reacted at 45°C for 35 minutes; the above operation is performed only once, and then dried to obtain the product.

[0096] Quality Inspection

[0097] 1. The specific aqueous polyurethane emulsion 8355 is used in the examples and comparative examples. The performance of the green environmentally friendly waterproof coatings in Examples 2-4 and Comparative Examples 1-5 is tested with reference to the standards of GB / T19250-2013 and GB / T 16777-2008. The specific test results are shown in the following table.

[0098] Table 1 Strength test results

[0099] category Tensile strength(MPa) Tear strength (N / mm) Adhesion strength (MPa) Example 2 7.6 40.3 2.7 Example 3 7.8 40.5 2.6 Example 4 8.2 42.7 2.8 Comparative Example 1 7.3 38.2 2.3 Comparative Example 2 6.2 33.4 2.0 Comparative Example 3 5.3 28.9 1.84 Comparative Example 4 8.0 42.5 2.8 Comparative Example 5 8.1 42.3 2.8

[0100] Table 2 Waterproof performance test

[0101]

[0102]

[0103] From Table 1 and Table 2, we can know that:

[0104] (1) Compared with Comparative Example 1, Example 4 performs better in terms of strength and waterproofness, indicating that wrapping nano-silicon dioxide on carbon fiber enhances the strength of the carbon fiber body and improves the hydrophobicity of the coating;

[0105] (2) Compared with Comparative Example 2, the strength of Example 4 is significantly improved, indicating that the addition of carbon fiber plays an important role in improving the strength of the coating, and the waterproofness of Example 4 is improved to a certain extent, indicating that the chain-net structure formed by the modified carbon fiber attached to the surface of the glass flakes is slightly better than the nano-silicon dioxide directly attached to the surface of the glass flakes in terms of anti-permeability;

[0106] (3) In Comparative Example 3, only modified glass flakes are used, and its waterproof effect is significantly poor; although Comparative Example 4 uses modified glass flakes and modified carbon fibers, its waterproof effect is not significantly improved because the modified carbon fibers cannot be attached to the modified glass flakes in large quantities to form a chain network structure to improve the anti-penetration performance.

[0107] (4) Compared with Comparative Example 5, the overall performance of Example 4 is slightly improved, indicating that repeated wrapping of nano-silica on carbon fiber is conducive to forming a dense nano-silica layer, which has a positive effect on improving strength and waterproofness.

[0108] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A green and environmentally friendly waterproof coating, characterized in that: The method is composed of the following raw materials in parts by weight: 60-80 parts of waterborne polyurethane emulsion, 20-30 parts of chain mesh glass flakes, 2-5 parts of film-forming aid, 1-3 parts of leveling agent, 1-2 parts of defoaming agent, and 0.5-1 parts of thickener; The film-forming aid is selected from propylene glycol butyl ether and benzyl alcohol; the leveling agent is selected from cellulose acetate-butyrate and polydimethylsiloxane; the thickener is selected from hydroxypropyl methylcellulose and hydroxyethyl cellulose; the defoamer is an organosilicon defoamer; The preparation method of the chain mesh glass flakes is as follows: S1, coating the surface of carbon fiber with a nano-silicon dioxide layer, treating it with a silane coupling agent, and obtaining a modified carbon fiber after drying; S2. Pour the dopamine alkaline solution and glass flakes into the reaction chamber, and allow air to continuously form bubbles through the bubbling plate and enter the reaction chamber for stirring, maintaining an aerobic alkaline environment, and react at room temperature for 2-3 hours; S3, pouring the modified carbon fiber into the reaction chamber and adding an appropriate amount of silane coupling agent, continuing the bubbling reaction for 3-5 hours to obtain a mixed solution containing chain-net glass flakes; S4, filtering, washing, and drying the mixed liquid containing the chain-net glass flakes to obtain the chain-net glass flakes; In step S1, the preparation method of the nano-silicon dioxide layer coated on the surface of the carbon fiber is as follows: disperse the carbon fiber in a silicate solution, spray 8wt% sulfuric acid solution on its surface after filtering, and react at 40-50°C for 30-40min; repeat the above operation 2-4 times, and then dry to obtain.

2. A green and environmentally friendly waterproof coating according to claim 1, characterized in that: The silicate solution is prepared by mixing 5% sodium silicate solution and 15wt% sodium chloride solution in a volume ratio of 3:

2.

3. A green and environmentally friendly waterproof coating according to claim 1, characterized in that: In steps S1-S2, the thickness of the glass flakes is 5-8 μm, and the diameter of the glass flakes is 200-250 μm; the length of the carbon fiber is 20-50 μm.

4. A green and environmentally friendly waterproof coating according to claim 1, characterized in that: In step S2, the dopamine base solution is prepared as follows: Tris hydrochloride is dissolved in deionized water, the pH is adjusted to 8.5, and then dopamine is added and ultrasonically dispersed to obtain the solution.

5. A green and environmentally friendly waterproof coating according to claim 4, characterized in that: The material-liquid ratio of Tris hydrochloride to deionized water is 1:1000 g / mL, and the mass ratio of Tris hydrochloride to dopamine is 1:

1.

6. A green and environmentally friendly waterproof coating according to claim 1, characterized in that: In steps S2-S3, the mass ratio of modified carbon fiber to glass flake is 1:(2-4); the volume ratio of silane coupling agent to dopamine alkaline solution is 1:

15.

7. The method for preparing the green and environmentally friendly waterproof coating according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Inject the waterborne polyurethane emulsion into a stirring tank, add a film-forming aid, a leveling agent and a defoaming agent into the stirring tank, and stir evenly; (2) The chain mesh glass flakes are added into a stirring kettle in batches for stirring and dispersion, and then a thickener is added and stirring is continued to obtain a green and environmentally friendly waterproof coating.

Citation Information

Patent Citations

  • Wear-resistant self-lubricating anticorrosive coating material, preparation method and applications thereof

    CN109836959A

  • Modified phenolic resin material and preparation method thereof

    CN111454536A